Stevens–Johnson Syndrome and Herpes Simplex Type 1 Infection during Adalimumab Therapy for Crohn’s Disease - Jenny Roselli; Tommaso Innocenti; Erica Nicola Lynch; Laura Parisio; Pasquale Apolito; Tommaso Mello; Giuseppe Macrì; Monica Milla; Maria Rosa Biagini; Mirko Tarocchi; Stefano Milani; Andrea Galli (Case Reports in Gastrointestinal Medicine)
Stevens–Johnson syndrome (SJS) is a severe mucocutaneous adverse drug reaction with a relatively high mortality rate. SJS is described during herpes simplex virus type 1 (HSV1) infection and, rarely, even during adalimumab therapy. We report the case of a patient with Crohn’s disease who developed SJS during an HSV1 infection and a contemporaneous anti-TNFα therapy with adalimumab. Remission was achieved with suspension of adalimumab and high doses of intravenous steroids and antivirals. Patients with HSV1 infection and on adalimumab therapy have a combined risk of SJS and should be monitored closely.